End-of-life in the operational functioning of public healthcare: ethical and legal issues - Basile, Giuseppe; De Nina, Angelo; Montana, Angelo; Negro, Francesca; Straccamore, Marco; Napoletano, Gabriele; Marinelli, Enrico (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: The article aims to outline the current scenario relative to the medical role in end-of-life issues. In order to do this, historical-legal references have been drawn upon relating to technical, legal and scientific thought and doctrine, as it has come down to us in the medical field through the evolution of ethical and philosophical frameworks. Methods: The authors have conducted a thorough analysis of end-of-life legislative initiatives, in Italy and across the EU, and court rulings to outline possible ways to harmonize and reconcile the current medical ethics frameworks with the needs and rights of all, especially the most vulnerable among us. To that end, the necessary operational choices and adjustments have not yet been made by our legal system, from a technical, as well as moral, standpoint. Results: An operational proposal has therefore been laid out to protect both healthcare providers and patients, in a relationship that goes beyond treatment in the strict sense, which prioritizes mutual needs as an integral part of a common, essential path.Conclusions: In order for doctors to consider themselves complete, they should in fact deal not only with life, but also with death.